TRANSFORMING ONLINE CHAT DATA INTO ARTICLES: EXPLORING THE STUDENTS’ WRITING QUALITIES AND DIFFICULTIES IN GENERATING AND ORGANIZING IDEAS - Wahyu Kyestiati Sumarno (English Language and Literature International Conference (ELLiC) Proceedings, 2021)
The Covid-19 pandemic has forced everyone to be skillful in using the technology willy-nilly. Consequently, training the students to take data digitally and then proceed them into any mode of reports became a necessary matter. This study will examine how students transform online chat data into articles, especially in terms of their writing qualities and their difficulties when generating and organizing ideas. Generating and organizing ideas play the primary role in the initial phase of the writing process, but a limited study is available in the literature that addresses this case. This descriptive study invited 66 students to answer the research questions by analyzing the questionnaires and evaluating their writings. The findings indicated that most students faced problems when generating and organizing ideas and that their articles' quality was still poor. Data analysis showed that the problems ranged from not fluent in writing in English, lack of practice to generate and organize the ideas, and not skilled at writing articles. Most of them did free writing and just write with the flow without thinking of the article's generic structure. Half of them were also unsure whether they used one of the suggested ways to generate and organize ideas. Some pedagogical implications were discussed, including stimulating the students' metacognitive skills during the process of writing and giving more explicit exercises to generate and organize ideas with frequent constructive feedback from the teachers.